Quantitative Angiographic Assessment of Aortic Regurgitation after Transcatheter Aortic Valve Implantation among Three Balloon-Expandable Valves - Hideyuki Kawashima; Rutao Wang; Darren Mylotte; Dariusz Jagielak; Frederico De Marco; Alfonso Ielasi; Yoshinobu Onuma; Peter den Heijer; Christian Juhl Terkelsen; William Wijns; Patrick W. Serruys; Osama Soliman (Ubiquity Press, 2021)
Objectives: The aim of the present analysis is to compare the quantitative angiographic aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) among three balloon-expandable valves. Background: Quantitative videodensitometric aortography is an objective, accurate, and reproducible tool for adjudication of AR following TAVI. Methods: This is a retrospective corelab analysis, independent from industry, of aortograms from patients treated with TAVI using the balloon-expandable Myval transcatheter heart valve (THV) (Meril Life Sciences Pvt. Ltd., India), Sapien 3, and XT THVs (Edwards Lifesciences, Irvine, CA, USA). The study comprised of 108 analyzable aortograms from consecutive patients in a multicenter European registry who underwent Myval THV implantation. The results of quantitative assessment of AR in the Sapien 3 THV (n = 397) and Sapien XT THV (n = 239) were retrieved from a published pooled database. Results: The Myval THV had the lowest proportion of patients with moderate or severe angiographic quantitative AR (2.8%) compared to the Sapien 3 THV (8.3%; p = 0.049) and Sapien XT THV (10.9%; p = 0.012). Furthermore, the Myval THV had the lowest mean angiographic quantitative AR (6.3 ± 6.3%), followed by Sapien 3 THV (7.6 ± 7.1%) and Sapien XT THV (8.8 ± 7.5%), and it was significantly lower than that of the Sapien XT THV (p = 0.006), but not significantly different from Sapien 3 THV (p = 0.246). Conclusion: The Myval THV, in comparison with other BEV's analyzed in our database, showed a lower occurrence of moderate or severe AR after TAVI. These results should be confirmed in prospective cohorts of randomized patients with head-to-head THV comparisons.